Wear-resistant antibacterial multilayer composite fabric and preparation method thereof

By introducing flame-retardant and antistatic composite materials and antibacterial finishing agents into composite fabrics, combined with the use of ecological cotton, the problem of insufficient antistatic, flame retardant and antibacterial properties of existing fabrics is solved, and wear-resistant, antibacterial, flame retardant and antibacterial properties are achieved. Increased antistatic versatility.

CN119348269AInactive Publication Date: 2025-01-24WUJIANG TUTAIKE TEXTILE & FINISHING CO LTD

Patent Information

Application Number
CN202411899274.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The antistatic and flame retardant properties of the outer structure of existing composite fabrics are insufficient, and the antibacterial properties of the inner structure also need to be improved.

Method used

It adopts a multi-layer composite fabric structure. The outer layer of fabric is introduced with flame-retardant and antistatic composite materials, including phosphate ester, polyaniline and graphene oxide, to improve antistatic and flame-retardant properties; the inner layer of fabric is treated with antibacterial finishing agent and uses nanometer Components such as zinc oxide and oleic acid amide improve antibacterial properties; the middle layer fabric uses ecological cotton to enhance thermal insulation properties.

Benefits of technology

It has improved the wear resistance, antibacterial, flame retardant and antistatic properties of the fabric, and improved the overall functionality and service life of the fabric.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119348269A_ABST
    Figure CN119348269A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of layered composite fabrics, in particular to a wear-resistant antibacterial multilayer composite fabric and a preparation method thereof. The wear-resistant antibacterial multi-layer composite fabric comprises three layers of structures including the inner layer fabric, the middle layer fabric and the outer layer fabric, the outer layer fabric adopts polyamide resin as a matrix raw material and has excellent wear resistance, the flame-retardant and antistatic properties of the polyamide fabric can be effectively improved by adding the flame-retardant and antistatic composite material, and the wear resistance of the fabric is improved. The inner-layer fabric is formed by spinning the cotton fibers and has good warm keeping comfort, the antibacterial performance of the inner-layer fabric can be improved through treatment of the antibacterial finishing agent, the ecological cotton is adopted as the middle-layer fabric and is light and warm, and the warm keeping performance of the composite fabric can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of layered composite fabrics, and in particular to a wear-resistant and antibacterial multi-layer composite fabric and a preparation method thereof. Background Art

[0002] With the continuous improvement of living standards, people have higher and higher functional requirements for clothing fabrics. For outdoor sportswear, the fabrics are required to be skin-friendly and comfortable, and also have good wear resistance. In the prior art, a multi-layer structure is often used to achieve the various properties of fabrics. For example, the inner layer of fabric is made of soft and skin-friendly raw materials such as cotton fiber, and the outer layer of fabric is made of highly wear-resistant polyamide. For high-altitude outdoor sportswear such as mountaineering clothes, a warm layer can also be set to prevent the risk of hypothermia caused by the low temperature in high-altitude areas. However, sweating after exercise can easily breed bacteria, so the inner layer of fabric needs to be treated with antibacterial treatment, and polyamide fabrics are prone to static electricity due to friction, which poses a safety hazard. At the same time, the flame retardant properties of the fabric need to be improved.

[0003] Chinese patent CN1306102C discloses an antibacterial cotton fiber or cotton fabric and a preparation method, wherein the cotton fiber or fabric is treated with alkali in an alkaline solution to form alkali cellulose, and then carboxymethylated to attach carboxymethyl groups to the fiber surface, and finally the carboxyl group reacts with zinc ions to generate carboxylic acid zinc salts to form zinc-containing cotton products with antibacterial effects. However, during the alkali treatment of the cotton fiber or fabric, the structure of the cotton fiber is easily destroyed, thereby affecting the strength and service life of the cotton fiber or fabric. Chinese patent CN103360755B discloses an antistatic flame-retardant nylon, which improves the electrical conductivity of polyamide fiber by adding germanium dioxide, and improves the flame retardant properties of polyamide fiber by adding antimony trioxide. However, the compatibility and dispersion uniformity between the inorganic conductive material and the inorganic flame retardant material and the polyamide fiber are poor, and the antistatic flame retardant properties need to be improved. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a wear-resistant and antibacterial multi-layer composite fabric and a preparation method thereof to solve the problems in the prior art that the antistatic performance and flame retardant performance of the outer layer structure of the composite fabric need to be improved and the antibacterial performance of the inner layer structure needs to be improved.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A method for preparing a wear-resistant and antibacterial multi-layer composite fabric comprises the following steps: Step 1, mixing pentaerythritol and phosphorus oxychloride, reacting, cooling, filtering, washing, and drying after the reaction is completed to obtain pentaerythritol bisphosphate diphosphoryl chloride; Step 2: adding melamine into deionized water, heating and dissolving, adjusting the pH value to 9-10, adding epoxy-modified graphene oxide, reacting, filtering, washing, and drying after the reaction is completed to obtain melamine-graphene oxide; Adding polyaniline to N-methylpyrrolidone, stirring and dissolving, adding melamine-graphene oxide and pyridine, ultrasonically dispersing, adding pentaerythritol diphosphate diphosphoryl chloride, reacting, cooling after the reaction, filtering, washing, and drying to obtain a flame retardant and antistatic composite material; Step 3, mixing the flame retardant antistatic composite material with the polyamide resin, and melt spinning to obtain the flame retardant antistatic polyamide fiber; Step 4, spinning the flame retardant antistatic polyamide fiber into yarn, and then spinning the yarn into fabric to obtain the flame retardant antistatic polyamide fiber fabric; Step 5, spinning the cotton fiber into yarn, and then spinning the yarn into fabric to obtain a cotton fiber fabric base cloth; The cotton fiber fabric base fabric is impregnated in an antibacterial finishing agent, double-impregnated and double-rolled, cured, washed, and dried to obtain an antibacterial cotton fiber fabric; The antibacterial cotton fiber fabric is used as the inner layer fabric, the ecological cotton is used as the middle layer fabric, and the flame-retardant antistatic polyamide fiber fabric is used as the outer layer fabric. The inner layer fabric, the middle layer fabric, and the outer layer fabric are compounded to obtain a wear-resistant and antibacterial multi-layer composite fabric.

[0006] Preferably, in step 1, the molar ratio of pentaerythritol to phosphorus oxychloride is 1:(2-2.2), and the reaction conditions are reflux reaction at 95-105° C. for 5-7 hours.

[0007] Preferably, in the step 2: when preparing melamine-graphene oxide, the mass ratio of melamine, deionized water and epoxy-modified graphene oxide is 12.6:(300-400):(8-10), and the reaction conditions are 85-95° C. for 5.5-6.5 h.

[0008] Preferably, the epoxy-modified graphene oxide is prepared by the following steps: Graphene oxide is added to an ethanol aqueous solution, and after ultrasonic dispersion, γ-glycidyloxypropyltrimethoxysilane is added dropwise for reaction. After the reaction is completed, the mixture is filtered, washed, and dried to obtain epoxy-modified graphene oxide.

[0009] Preferably, the mass ratio of the graphene oxide, the ethanol aqueous solution and γ-glycidyloxypropyltrimethoxysilane is 20:(400-600):(8-12), and the reaction conditions are reflux reaction at a temperature of 70-80° C. for 8-12 hours.

[0010] Preferably, the ethanol aqueous solution is 75 wt % ethanol aqueous solution.

[0011] Preferably, in the step 2: when preparing the flame retardant antistatic composite material, the mass ratio of polyaniline, N-methylpyrrolidone, melamine-graphene oxide, pyridine, and pentaerythritol bisphosphate diphosphoryl chloride is (72.7-76.3):(1000-1500):(15-20):(8-12):(20-30), and the reaction conditions are 60-80°C for 8-10h.

[0012] Preferably, in step three: the mass ratio of the flame retardant antistatic composite material to the polyamide resin is (6-10):100, and the melt spinning temperature is 260-280°C.

[0013] Preferably, in step 4: the yarn count of the yarn is 30-50S (English count), and the weight of the flame retardant and antistatic polyamide fiber fabric is 180-220g / m 2 .

[0014] Preferably, in step 5: the yarn count of the yarn is 40-60S, and the weight of the cotton fiber fabric base cloth is 160-180g / m 2 .

[0015] Preferably, in step five: the bath ratio of the cotton fiber fabric base cloth to the antibacterial finishing agent is 1:(15-25), and the curing condition is irradiation under ultraviolet light with a wavelength of 254nm for 5-10min.

[0016] Preferably, the antibacterial finishing agent is prepared by the following steps: S1. Add thionyl chloride dropwise to oleic acid under stirring, react after the addition is complete, and purify after the reaction to obtain oleic acid chloride; S2. adding diallylamine to toluene, stirring and dispersing, and then dropping oleic acid chloride, and after the dropping is complete, reacting, and after the reaction is complete, purifying to obtain oleic acid amide; S3. Add γ-chloropropylmethyldimethoxysilane to an ethanol aqueous solution, and after ultrasonic dispersion, add nano zinc oxide to react. After the reaction is completed, filter, wash, and dry to obtain chlorinated modified nano zinc oxide; The chlorinated modified nano zinc oxide is added to ethanol, ultrasonically dispersed, and then oleic acid amide and potassium iodide are added to react. After the reaction is completed, the reaction is filtered, washed, and dried to obtain a quaternary ammonium antibacterial agent. S4. Add the quaternary ammonium antibacterial agent and azobisisobutyronitrile into ethyl acetate, stir and disperse, and obtain an antibacterial finishing agent.

[0017] Preferably, in S1, the molar ratio of oleic acid to thionyl chloride is 1:(1-1.2), and the reaction conditions are 1.5-2.5h at 25-35°C; in S2, the mass ratio of toluene to diallylamine is 1:(10-20), the molar ratio of diallylamine to oleic acid chloride is (1-1.1):1, and the reaction conditions are reflux reaction at 110-120°C for 8-12h; in S3, when preparing chlorinated modified nano zinc oxide, the mass ratio of γ-chloropropylmethyldimethoxysilane, ethanol aqueous solution, and nano zinc oxide is (15-20) :(250-350):81, the reaction conditions are 6-10h at 70-80°C. When preparing the quaternary ammonium antibacterial agent, the mass ratio of chlorinated modified nano zinc oxide, ethanol, oleic acid amide and potassium iodide is (8.8-9.2):(80-120):(36.2-38):(0.05-0.11), and the reaction conditions are 20-30h at 75-85°C; in S4: the mass ratio of quaternary ammonium antibacterial agent, ethyl acetate and azobisisobutyronitrile is (8-13):(150-200):(0.06-0.1).

[0018] The invention also discloses a wear-resistant and antibacterial multi-layer composite fabric prepared by adopting the above-mentioned method for preparing the wear-resistant and antibacterial multi-layer composite fabric.

[0019] Compared with the prior art, the present invention has the following beneficial effects: The wear-resistant and antibacterial multi-layer composite fabric of the present invention comprises an inner layer fabric, an intermediate layer fabric and an outer layer fabric, wherein the outer layer fabric adopts polyamide resin as a matrix material and has excellent wear resistance. By adding a flame-retardant and antistatic composite material, the flame retardant and antistatic properties of the polyamide fabric can be effectively improved. The inner layer fabric is spun from cotton fiber and has good warmth retention and comfort. The antibacterial properties of the inner layer fabric can be improved by treatment with an antibacterial finishing agent. Ecological cotton is adopted as the intermediate layer fabric, which is light and warm, and can effectively improve the warmth retention properties of the composite fabric. In the present invention, when preparing the outer fabric, flame retardant components phosphate, melamine and graphene oxide are introduced into the polyamide resin, so that the outer fabric has good flame retardant properties. At the same time, the graphene oxide has good electrical conductivity and synergistically acts with the antistatic component polyaniline to give the outer fabric good antistatic properties. In the preparation process of the flame retardant and antistatic composite material, the amino group on the melamine molecule reacts with the epoxy group on the epoxy-modified graphene oxide to obtain melamine-graphene oxide, thereby achieving chemical bonding between melamine and graphene oxide. Furthermore, melamine-graphene oxide and polyaniline react with the phosphorus oxychloride group on the pentaerythritol bisphosphate diphosphoryl chloride molecule through the amino group and imino group contained in the melamine-graphene oxide and polyaniline molecules, thereby achieving chemical crosslinking between melamine-graphene oxide, polyaniline and pentaerythritol bisphosphate diphosphoryl chloride. Through the entanglement of the crosslinked product with the polyamide molecular chain, the compatibility and dispersion uniformity of each effective component in the polyamide resin are improved, and the flame retardant property and antistatic effect are good. In the present invention, when preparing the inner layer fabric, the antibacterial component of the antibacterial finishing agent used is nano zinc oxide, and the higher fatty acid oleic acid is introduced at the same time, so that the softness of the inner layer fabric can be improved, oleic acid reacts with thionyl chloride to obtain oleic acid chloride, the acyl chloride group on the oleic acid chloride molecule reacts with the imino group on the diallylamine molecule to convert the imino group into a tertiary amine, the nano zinc oxide reacts with gamma-chloropropylmethyldimethoxysilane to obtain chlorinated modified nano zinc oxide, the chlorinated modified nano zinc oxide reacts with the tertiary amine to generate an antibacterial quaternary ammonium salt, and the antibacterial property is further improved, and the carbon-carbon double bonds in the oleic acid molecules and the carbon-carbon double bonds on the diallylamine molecules can be cured and cross-linked in the pores and surface of the cotton fiber fabric base cloth under the action of a photoinitiator and under ultraviolet irradiation, and the fabric is not easy to fall off during use and washing, and the antibacterial property is stable and durable. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The present invention is a flow chart of the preparation process of the flame retardant and antistatic polyamide fiber; Figure 2 The result bar graph is a result of measuring the charge surface density of the flame-retardant and antistatic polyamide fiber fabrics prepared in Examples 2-6 of the present invention and Comparative Examples 1-2; Figure 3 A bar graph showing the results of measuring the limiting oxygen index of the flame-retardant and antistatic polyamide fiber fabrics prepared in Examples 2-6 of the present invention and Comparative Examples 1-2; Figure 4 A bar graph showing the results of measuring the antibacterial rates of the antibacterial cotton fiber fabrics prepared in Examples 2-6 of the present invention and Comparative Examples 1-2 before washing; Figure 5 This is a bar chart showing the results of measuring the antibacterial rates of the antibacterial cotton fiber fabrics prepared in Examples 2-6 of the present invention and Comparative Examples 1-2 after washing 50 times. DETAILED DESCRIPTION

[0021] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0022] Example 1 This embodiment discloses a method for preparing an antibacterial finishing agent, comprising the following steps: S1. Under stirring conditions of 300 r / min, thionyl chloride was added dropwise to oleic acid, the molar ratio of oleic acid to thionyl chloride was 1:1.1, and the dropping speed of thionyl chloride was 0.5 g / min. After the addition was completed, the reaction was carried out at 30° C. for 2 h. After the reaction was completed, the unreacted thionyl chloride was removed by rotary evaporation at 45° C. to obtain oleic acid chloride; S2. Diallylamine was added to toluene, the mass ratio of toluene to diallylamine was 1:15, and after stirring and dispersing at a speed of 200 r / min for 30 min, oleic acid chloride was added dropwise, the molar ratio of diallylamine to oleic acid chloride was 1.05:1, and the dropping speed of oleic acid chloride was 2 g / min. After the addition was completed, the reaction was refluxed at 115° C. for 10 h. After the reaction was completed, the solvent toluene and the unreacted diallylamine were removed by rotary evaporation at 80° C. to obtain oleic acid amide; S3. Add γ-chloropropylmethyldimethoxysilane to 75%wt ethanol aqueous solution, ultrasonically disperse at a frequency of 50kHz for 30 minutes, add nano zinc oxide, the mass ratio of γ-chloropropylmethyldimethoxysilane, 75%wt ethanol aqueous solution, and nano zinc oxide is 18:300:81, react at 75°C for 8h, filter after the reaction, wash with ethanol 3 times, and place in a vacuum drying oven at 50°C for 24h to obtain chlorinated modified nano zinc oxide; The chlorinated nano zinc oxide was added to ethanol, and after ultrasonic dispersion at a frequency of 50kHz for 30 minutes, oleic acid amide and potassium iodide were added, and the mass ratio of the chlorinated nano zinc oxide, ethanol, oleic acid amide and potassium iodide was 9:100:37:0.08. The reaction was carried out at a temperature of 80°C for 24 hours. After the reaction was completed, the mixture was filtered, washed with ethanol for 3 times, and dried in a vacuum drying oven at 50°C for 24 hours to obtain a quaternized antibacterial agent. S4. Add the quaternary ammonium antibacterial agent and azobisisobutyronitrile to ethyl acetate, the mass ratio of the quaternary ammonium antibacterial agent, ethyl acetate and azobisisobutyronitrile is 10:180:0.08, and stir and disperse at a speed of 300 r / min for 30 minutes to obtain an antibacterial finishing agent.

[0023] Example 2 This embodiment discloses a method for preparing a wear-resistant and antibacterial multi-layer composite fabric, comprising the following steps: Step 1, pentaerythritol and phosphorus oxychloride are mixed, the molar ratio of pentaerythritol to phosphorus oxychloride is 1:2, and reflux reaction is carried out at 95°C for 7 hours. After the reaction is completed, the mixture is cooled to 0°C and filtered. The filtered residue is first washed with deionized water for 3 times, then washed with dichloromethane for 3 times, and dried in a vacuum drying oven at 50°C to constant weight to obtain pentaerythritol bisphosphate diphosphoryl chloride; Step 2: Add melamine to deionized water, heat and dissolve at 85°C, adjust the pH value to 9 with 1 mol / L sodium hydroxide aqueous solution, add epoxy-modified graphene oxide, the mass ratio of melamine, deionized water and epoxy-modified graphene oxide is 12.6:300:8, react at 85°C for 6.5h, filter while hot after the reaction, wash the filtered residue with 100°C deionized water for 5 times, and dry it in a vacuum drying oven at 50°C for 24h to obtain melamine-graphene oxide; Wherein, the epoxy-modified graphene oxide is prepared by the following steps: The graphene oxide was added to a 75wt% ethanol aqueous solution, and after ultrasonic dispersion at a frequency of 50kHz for 30min, γ-glycidyloxypropyltrimethoxysilane was added dropwise, the mass ratio of graphene oxide, 75wt% ethanol aqueous solution, and γ-glycidyloxypropyltrimethoxysilane was 20:500:10, and the dropping time of γ-glycidyloxypropyltrimethoxysilane was 30min. After the dropping was completed, the reaction was refluxed at 75°C for 10h. After the reaction was completed, the reaction was filtered, washed with ethanol 3 times, and dried in a vacuum drying oven at 50°C for 24h to obtain epoxy-modified graphene oxide; Add polyaniline to N-methylpyrrolidone, stir and dissolve, add melamine-graphene oxide and pyridine, ultrasonically disperse at a frequency of 50kHz for 30 minutes, add pentaerythritol bisphosphate diphosphoryl chloride, the mass ratio of polyaniline, N-methylpyrrolidone, melamine-graphene oxide, pyridine and pentaerythritol bisphosphate diphosphoryl chloride is 72.7:1000:15:8:20, react at 60°C for 10 hours, cool to 0°C after the reaction, filter, wash the filtered residue with deionized water for 3 times, and dry it in a vacuum drying oven at 50°C for 24 hours to obtain a flame retardant and antistatic composite material; Step 3, mixing the flame retardant antistatic composite material with a polyamide resin, wherein the mass ratio of the flame retardant antistatic composite material to the polyamide resin is 6:100, and melt spinning at a melt spinning temperature of 260° C. to obtain a flame retardant antistatic polyamide fiber; Step 4: Spin the flame retardant antistatic polyamide fiber into yarn, the yarn count of the yarn is 30S, and then spin the yarn into fabric through a shuttle weaving process to obtain a flame retardant antistatic polyamide fiber fabric, the weight of the flame retardant antistatic polyamide fiber fabric is 220g / m 2 ; Step 5: Spin the cotton fiber into yarn with a yarn count of 40S, and then spin the yarn into fabric through a knitting process to obtain a cotton fiber fabric base fabric with a gram weight of 180g / m 2 ; The cotton fiber fabric base fabric was impregnated in the antibacterial finishing agent, the bath ratio of the cotton fiber fabric base fabric to the antibacterial finishing agent was 1:15, two immersions and two rollings were performed, and the rolling rate was 80%. The base fabric was irradiated under ultraviolet light with a wavelength of 254 nm for 5 minutes for curing. After the curing was completed, the base fabric was washed with clean water for 3 times, and dried in a vacuum drying oven at 50° C. for 10 hours to obtain the antibacterial cotton fiber fabric. Wherein, the antibacterial finishing agent is the antibacterial finishing agent prepared in Example 1; The antibacterial cotton fiber fabric is used as the inner layer fabric, the ecological cotton is used as the middle layer fabric, and the flame-retardant antistatic polyamide fiber fabric is used as the outer layer fabric. The inner layer fabric, the middle layer fabric, and the outer layer fabric are sewn and compounded by polyester thread to obtain a wear-resistant and antibacterial multi-layer composite fabric.

[0024] Example 3 This embodiment discloses a method for preparing a wear-resistant and antibacterial multi-layer composite fabric, comprising the following steps: Step 1, pentaerythritol and phosphorus oxychloride are mixed, the molar ratio of pentaerythritol to phosphorus oxychloride is 1:2.2, and reflux reaction is carried out at 105° C. for 5 hours. After the reaction is completed, the mixture is cooled to 0° C. and filtered. The filtered residue is first washed with deionized water for 3 times, then washed with dichloromethane for 3 times, and dried in a vacuum drying oven at 50° C. to constant weight to obtain pentaerythritol bisphosphate diphosphoryl chloride; Step 2: Add melamine to deionized water, heat and dissolve at 95°C, adjust the pH value to 10 with 1 mol / L sodium hydroxide aqueous solution, add epoxy-modified graphene oxide, the mass ratio of melamine, deionized water and epoxy-modified graphene oxide is 12.6:400:10, react at 95°C for 5.5h, filter while hot after the reaction, wash the filtered residue with 100°C deionized water for 5 times, and dry it in a vacuum drying oven at 50°C for 24h to obtain melamine-graphene oxide; Wherein, the preparation method of epoxy-modified graphene oxide is the same as that of Example 2; Add polyaniline to N-methylpyrrolidone, stir and dissolve, add melamine-graphene oxide and pyridine, ultrasonically disperse at a frequency of 50kHz for 30 minutes, add pentaerythritol bisphosphate diphosphoryl chloride, the mass ratio of polyaniline, N-methylpyrrolidone, melamine-graphene oxide, pyridine and pentaerythritol bisphosphate diphosphoryl chloride is 76.3:1500:20:12:30, react at 80°C for 8h, cool to 0°C after the reaction, filter, wash the filtered residue with deionized water for 3 times, and dry it in a vacuum drying oven at 50°C for 24h to obtain a flame retardant and antistatic composite material; Step 3, mixing the flame retardant antistatic composite material with a polyamide resin, wherein the mass ratio of the flame retardant antistatic composite material to the polyamide resin is 10:100, and melt spinning at a melt spinning temperature of 280° C. to obtain a flame retardant antistatic polyamide fiber; Step 4: Spin the flame retardant antistatic polyamide fiber into yarn, the yarn count of the yarn is 50S, and then spin the yarn into fabric through a shuttle weaving process to obtain a flame retardant antistatic polyamide fiber fabric, the weight of the flame retardant antistatic polyamide fiber fabric is 180g / m 2 ; Step 5: Spin the cotton fiber into yarn with a yarn count of 60S, and then spin the yarn into fabric through a knitting process to obtain a cotton fiber fabric base fabric with a gram weight of 160g / m 2 ; The cotton fiber fabric base fabric was impregnated in the antibacterial finishing agent, the bath ratio of the cotton fiber fabric base fabric to the antibacterial finishing agent was 1:25, two immersions and two rollings were performed, the rolling rate was 90%, and the base fabric was irradiated under ultraviolet light with a wavelength of 254nm for 10 minutes for curing. After the curing was completed, the base fabric was washed with clean water for 3 times, and dried in a vacuum drying oven at 50°C for 10 hours to obtain the antibacterial cotton fiber fabric; Wherein, the antibacterial finishing agent is the antibacterial finishing agent prepared in Example 1; The antibacterial cotton fiber fabric is used as the inner layer fabric, the ecological cotton is used as the middle layer fabric, and the flame-retardant antistatic polyamide fiber fabric is used as the outer layer fabric. The inner layer fabric, the middle layer fabric, and the outer layer fabric are sewn and compounded by polyester thread to obtain a wear-resistant and antibacterial multi-layer composite fabric.

[0025] Example 4 This embodiment discloses a method for preparing a wear-resistant and antibacterial multi-layer composite fabric, comprising the following steps: Step 1, pentaerythritol and phosphorus oxychloride are mixed, the molar ratio of pentaerythritol to phosphorus oxychloride is 1:2.05, and reflux reaction is carried out at 100° C. for 6 hours. After the reaction is completed, the mixture is cooled to 0° C. and filtered. The filtered residue is first washed with deionized water for 3 times, then washed with dichloromethane for 3 times, and dried in a vacuum drying oven at 50° C. to constant weight to obtain pentaerythritol bisphosphate diphosphoryl chloride; Step 2: Add melamine to deionized water, heat and dissolve at 90°C, adjust the pH value to 9.5 with 1 mol / L sodium hydroxide aqueous solution, add epoxy-modified graphene oxide, the mass ratio of melamine, deionized water and epoxy-modified graphene oxide is 12.6:325:8.5, react at 90°C for 6h, filter while hot after the reaction, wash the filtered residue with 100°C deionized water for 5 times, and dry it in a vacuum drying oven at 50°C for 24h to obtain melamine-graphene oxide; Wherein, the preparation method of epoxy-modified graphene oxide is the same as that of Example 2; Add polyaniline to N-methylpyrrolidone, stir and dissolve, add melamine-graphene oxide and pyridine, ultrasonically disperse at a frequency of 50kHz for 30 minutes, add pentaerythritol bisphosphate diphosphoryl chloride, the mass ratio of polyaniline, N-methylpyrrolidone, melamine-graphene oxide, pyridine and pentaerythritol bisphosphate diphosphoryl chloride is 73.6:1150:16.5:9:22, react at 70°C for 9 hours, cool to 0°C after the reaction, filter, wash the filtered residue with deionized water for 3 times, and dry it in a vacuum drying oven at 50°C for 24 hours to obtain a flame retardant and antistatic composite material; Step 3, mixing the flame retardant antistatic composite material with a polyamide resin, wherein the mass ratio of the flame retardant antistatic composite material to the polyamide resin is 7:100, and melt spinning at a melt spinning temperature of 270° C. to obtain a flame retardant antistatic polyamide fiber; Step 4: Spin the flame retardant antistatic polyamide fiber into yarn, the yarn count of the yarn is 40S, and then spin the yarn into fabric through a shuttle weaving process to obtain a flame retardant antistatic polyamide fiber fabric, the weight of the flame retardant antistatic polyamide fiber fabric is 200g / m 2 ; Step 5: Spin the cotton fiber into yarn with a yarn count of 50S, and then spin the yarn into fabric through a knitting process to obtain a cotton fiber fabric base fabric with a gram weight of 170g / m 2 ; The cotton fiber fabric base fabric was impregnated in the antibacterial finishing agent, the bath ratio of the cotton fiber fabric base fabric to the antibacterial finishing agent was 1:20, two immersions and two rollings were performed, and the rolling rate was 85%. The base fabric was irradiated under ultraviolet light with a wavelength of 254 nm for 8 minutes for curing. After the curing was completed, the base fabric was washed with clean water for 3 times, and dried in a vacuum drying oven at 50° C. for 10 hours to obtain the antibacterial cotton fiber fabric. Wherein, the antibacterial finishing agent is the antibacterial finishing agent prepared in Example 1; The antibacterial cotton fiber fabric is used as the inner layer fabric, the ecological cotton is used as the middle layer fabric, and the flame-retardant antistatic polyamide fiber fabric is used as the outer layer fabric. The inner layer fabric, the middle layer fabric, and the outer layer fabric are sewn and compounded by polyester thread to obtain a wear-resistant and antibacterial multi-layer composite fabric.

[0026] Example 5 This embodiment discloses a method for preparing a wear-resistant and antibacterial multi-layer composite fabric, comprising the following steps: Step 1, pentaerythritol and phosphorus oxychloride are mixed, the molar ratio of pentaerythritol to phosphorus oxychloride is 1:2.1, and reflux reaction is carried out at 100° C. for 6 hours. After the reaction is completed, the mixture is cooled to 0° C. and filtered. The filtered residue is first washed with deionized water for 3 times, then washed with dichloromethane for 3 times, and dried in a vacuum drying oven at 50° C. to constant weight to obtain pentaerythritol bisphosphate diphosphoryl chloride; Step 2: Add melamine to deionized water, heat and dissolve at 90°C, adjust the pH value to 9.5 with 1 mol / L sodium hydroxide aqueous solution, add epoxy-modified graphene oxide, the mass ratio of melamine, deionized water and epoxy-modified graphene oxide is 12.6:350:9, react at 90°C for 6h, filter while hot after the reaction, wash the filtered residue with 100°C deionized water for 5 times, and dry it in a vacuum drying oven at 50°C for 24h to obtain melamine-graphene oxide; Wherein, the preparation method of epoxy-modified graphene oxide is the same as that of Example 2; Add polyaniline to N-methylpyrrolidone, stir and dissolve, add melamine-graphene oxide and pyridine, ultrasonically disperse at a frequency of 50kHz for 30 minutes, add pentaerythritol bisphosphate diphosphoryl chloride, the mass ratio of polyaniline, N-methylpyrrolidone, melamine-graphene oxide, pyridine and pentaerythritol bisphosphate diphosphoryl chloride is 74.5:1300:18:10:25, react at 70°C for 9 hours, cool to 0°C after the reaction, filter, wash the filtered residue with deionized water for 3 times, and dry it in a vacuum drying oven at 50°C for 24 hours to obtain a flame retardant and antistatic composite material; Step 3, mixing the flame retardant antistatic composite material with a polyamide resin, wherein the mass ratio of the flame retardant antistatic composite material to the polyamide resin is 8:100, and melt spinning at a melt spinning temperature of 270° C. to obtain a flame retardant antistatic polyamide fiber; Step 4: Spin the flame retardant antistatic polyamide fiber into yarn, the yarn count of the yarn is 40S, and then spin the yarn into fabric through a shuttle weaving process to obtain a flame retardant antistatic polyamide fiber fabric, the weight of the flame retardant antistatic polyamide fiber fabric is 200g / m 2 ; Step 5: Spin the cotton fiber into yarn with a yarn count of 50S, and then spin the yarn into fabric through a knitting process to obtain a cotton fiber fabric base fabric with a gram weight of 170g / m 2 ; The cotton fiber fabric base fabric was impregnated in the antibacterial finishing agent, the bath ratio of the cotton fiber fabric base fabric to the antibacterial finishing agent was 1:20, two immersions and two rollings were performed, and the rolling rate was 85%. The base fabric was irradiated under ultraviolet light with a wavelength of 254 nm for 8 minutes for curing. After the curing was completed, the base fabric was washed with clean water for 3 times, and dried in a vacuum drying oven at 50° C. for 10 hours to obtain the antibacterial cotton fiber fabric. Wherein, the antibacterial finishing agent is the antibacterial finishing agent prepared in Example 1; The antibacterial cotton fiber fabric is used as the inner layer fabric, the ecological cotton is used as the middle layer fabric, and the flame-retardant antistatic polyamide fiber fabric is used as the outer layer fabric. The inner layer fabric, the middle layer fabric, and the outer layer fabric are sewn and compounded by polyester thread to obtain a wear-resistant and antibacterial multi-layer composite fabric.

[0027] Example 6 This embodiment discloses a method for preparing a wear-resistant and antibacterial multi-layer composite fabric, comprising the following steps: Step 1, pentaerythritol and phosphorus oxychloride are mixed, the molar ratio of pentaerythritol to phosphorus oxychloride is 1:2.15, and reflux reaction is carried out at 100° C. for 6 hours. After the reaction is completed, the mixture is cooled to 0° C. and filtered. The filtered residue is first washed with deionized water for 3 times, then washed with dichloromethane for 3 times, and dried in a vacuum drying oven at 50° C. to constant weight to obtain pentaerythritol bisphosphate diphosphoryl chloride; Step 2: Add melamine to deionized water, heat and dissolve at 90°C, adjust the pH value to 9.5 with 1 mol / L sodium hydroxide aqueous solution, add epoxy-modified graphene oxide, the mass ratio of melamine, deionized water and epoxy-modified graphene oxide is 12.6:380:9.5, react at 90°C for 6h, filter while hot after the reaction, wash the filtered residue with 100°C deionized water for 5 times, and dry it in a 50°C vacuum drying oven for 24h to obtain melamine-graphene oxide; Wherein, the preparation method of epoxy-modified graphene oxide is the same as that of Example 2; Add polyaniline to N-methylpyrrolidone, stir and dissolve, add melamine-graphene oxide and pyridine, ultrasonically disperse at a frequency of 50kHz for 30 minutes, add pentaerythritol bisphosphate diphosphoryl chloride, the mass ratio of polyaniline, N-methylpyrrolidone, melamine-graphene oxide, pyridine and pentaerythritol bisphosphate diphosphoryl chloride is 75.4:1400:19:11:27, react at 70°C for 9 hours, cool to 0°C after the reaction, filter, wash the filtered residue with deionized water for 3 times, and dry it in a vacuum drying oven at 50°C for 24 hours to obtain a flame retardant and antistatic composite material; Step 3, mixing the flame retardant antistatic composite material with a polyamide resin, wherein the mass ratio of the flame retardant antistatic composite material to the polyamide resin is 9:100, and melt spinning at a melt spinning temperature of 270° C. to obtain a flame retardant antistatic polyamide fiber; Step 4: Spin the flame retardant antistatic polyamide fiber into yarn, the yarn count of the yarn is 40S, and then spin the yarn into fabric through a shuttle weaving process to obtain a flame retardant antistatic polyamide fiber fabric, the weight of the flame retardant antistatic polyamide fiber fabric is 200g / m 2 ; Step 5: Spin the cotton fiber into yarn with a yarn count of 50S, and then spin the yarn into fabric through a knitting process to obtain a cotton fiber fabric base fabric with a gram weight of 170g / m 2 ; The cotton fiber fabric base fabric was impregnated in the antibacterial finishing agent, the bath ratio of the cotton fiber fabric base fabric to the antibacterial finishing agent was 1:20, two immersions and two rollings were performed, and the rolling rate was 85%. The base fabric was irradiated under ultraviolet light with a wavelength of 254 nm for 8 minutes for curing. After the curing was completed, the base fabric was washed with clean water for 3 times, and dried in a vacuum drying oven at 50° C. for 10 hours to obtain the antibacterial cotton fiber fabric. Wherein, the antibacterial finishing agent is the antibacterial finishing agent prepared in Example 1; The antibacterial cotton fiber fabric is used as the inner layer fabric, the ecological cotton is used as the middle layer fabric, and the flame-retardant antistatic polyamide fiber fabric is used as the outer layer fabric. The inner layer fabric, the middle layer fabric, and the outer layer fabric are sewn and compounded by polyester thread to obtain a wear-resistant and antibacterial multi-layer composite fabric.

[0028] Comparative Example 1 This comparative example discloses a method for preparing a wear-resistant and antibacterial multi-layer composite fabric, comprising the following steps: Step 1, pentaerythritol and phosphorus oxychloride are mixed, the molar ratio of pentaerythritol to phosphorus oxychloride is 1:2, and reflux reaction is carried out at 95°C for 7 hours. After the reaction is completed, the mixture is cooled to 0°C and filtered. The filtered residue is first washed with deionized water for 3 times, then washed with dichloromethane for 3 times, and dried in a vacuum drying oven at 50°C to constant weight to obtain pentaerythritol bisphosphate diphosphoryl chloride; Step 2: mixing pentaerythritol bisphosphate diphosphoryl chloride, polyaniline, melamine, graphene oxide and polyamide resin, wherein the mass ratio of pentaerythritol bisphosphate diphosphoryl chloride, polyaniline, melamine, graphene oxide and polyamide resin is 1.1:4.1:0.5:0.3:100, and melt spinning at a melt spinning temperature of 260° C. to obtain flame retardant antistatic polyamide fiber; Step 3: Spin the flame retardant antistatic polyamide fiber into yarn, the yarn count of the yarn is 30S, and then spin the yarn into fabric through a shuttle weaving process to obtain a flame retardant antistatic polyamide fiber fabric, the weight of the flame retardant antistatic polyamide fiber fabric is 220g / m2 ; Step 4: Spin the cotton fiber into yarn with a yarn count of 40S, and then spin the yarn into fabric through a knitting process to obtain a cotton fiber fabric base fabric with a gram weight of 180g / m 2 ; The cotton fiber fabric base fabric was impregnated in the antibacterial finishing agent, the bath ratio of the cotton fiber fabric base fabric to the antibacterial finishing agent was 1:15, two immersions and two rollings were performed, and the rolling rate was 80%. The base fabric was irradiated under ultraviolet light with a wavelength of 254 nm for 5 minutes for curing. After the curing was completed, the base fabric was washed with clean water for 3 times, and dried in a vacuum drying oven at 50° C. for 10 hours to obtain the antibacterial cotton fiber fabric. Wherein, the antibacterial finishing agent is the antibacterial finishing agent prepared in Example 1; The antibacterial cotton fiber fabric is used as the inner layer fabric, the ecological cotton is used as the middle layer fabric, and the flame-retardant antistatic polyamide fiber fabric is used as the outer layer fabric. The inner layer fabric, the middle layer fabric, and the outer layer fabric are sewn and compounded by polyester thread to obtain a wear-resistant and antibacterial multi-layer composite fabric.

[0029] Comparative Example 2 This comparative example discloses a method for preparing a wear-resistant and antibacterial multi-layer composite fabric, comprising the following steps: Step 1, pentaerythritol and phosphorus oxychloride are mixed, the molar ratio of pentaerythritol to phosphorus oxychloride is 1:2, and reflux reaction is carried out at 95°C for 7 hours. After the reaction is completed, the mixture is cooled to 0°C and filtered. The filtered residue is first washed with deionized water for 3 times, then washed with dichloromethane for 3 times, and dried in a vacuum drying oven at 50°C to constant weight to obtain pentaerythritol bisphosphate diphosphoryl chloride; Step 2: Add melamine to deionized water, heat and dissolve at 85°C, adjust the pH value to 9 with 1 mol / L sodium hydroxide aqueous solution, add epoxy-modified graphene oxide, the mass ratio of melamine, deionized water and epoxy-modified graphene oxide is 12.6:300:8, react at 85°C for 6.5h, filter while hot after the reaction, wash the filtered residue with 100°C deionized water for 5 times, and dry it in a vacuum drying oven at 50°C for 24h to obtain melamine-graphene oxide; Wherein, the preparation method of epoxy-modified graphene oxide is the same as that of Example 2; Add polyaniline to N-methylpyrrolidone, stir and dissolve, add melamine-graphene oxide and pyridine, ultrasonically disperse at a frequency of 50kHz for 30 minutes, add pentaerythritol bisphosphate diphosphoryl chloride, the mass ratio of polyaniline, N-methylpyrrolidone, melamine-graphene oxide, pyridine and pentaerythritol bisphosphate diphosphoryl chloride is 72.7:1000:15:8:20, react at 60°C for 10 hours, cool to 0°C after the reaction, filter, wash the filtered residue with deionized water for 3 times, and dry it in a vacuum drying oven at 50°C for 24 hours to obtain a flame retardant and antistatic composite material; Step 3, mixing the flame retardant antistatic composite material with a polyamide resin, wherein the mass ratio of the flame retardant antistatic composite material to the polyamide resin is 6:100, and melt spinning at a melt spinning temperature of 260° C. to obtain a flame retardant antistatic polyamide fiber; Step 4: Spin the flame retardant antistatic polyamide fiber into yarn, the yarn count of the yarn is 30S, and then spin the yarn into fabric through a shuttle weaving process to obtain a flame retardant antistatic polyamide fiber fabric, the weight of the flame retardant antistatic polyamide fiber fabric is 220g / m 2 ; Step 5: Spin the cotton fiber into yarn with a yarn count of 40S, and then spin the yarn into fabric through a knitting process to obtain a cotton fiber fabric base fabric with a gram weight of 180g / m 2 ; The cotton fiber fabric base fabric was impregnated in the antibacterial finishing agent, the bath ratio of the cotton fiber fabric base fabric to the antibacterial finishing agent was 1:15, two immersions and two rollings were performed, and the rolling rate was 80%. The base fabric was irradiated under ultraviolet light with a wavelength of 254 nm for 5 minutes for curing. After the curing was completed, the base fabric was washed with clean water for 3 times, and dried in a vacuum drying oven at 50° C. for 10 hours to obtain the antibacterial cotton fiber fabric. Wherein, the antibacterial finishing agent is prepared by the following steps: S1. Under stirring conditions of 300 r / min, thionyl chloride was added dropwise to oleic acid, the molar ratio of oleic acid to thionyl chloride was 1:1.1, and the dropping speed of thionyl chloride was 0.5 g / min. After the addition was completed, the reaction was carried out at 30° C. for 2 h. After the reaction was completed, the unreacted thionyl chloride was removed by rotary evaporation at 45° C. to obtain oleic acid chloride; S2. Diallylamine was added to toluene, the mass ratio of toluene to diallylamine was 1:15, and after stirring and dispersing at a speed of 200 r / min for 30 min, oleic acid chloride was added dropwise, the molar ratio of diallylamine to oleic acid chloride was 1.05:1, and the dropping speed of oleic acid chloride was 2 g / min. After the addition was completed, the reaction was refluxed at 115° C. for 10 h. After the reaction was completed, the solvent toluene and the unreacted diallylamine were removed by rotary evaporation at 80° C. to obtain oleic acid amide; S3. Add γ-chloropropylmethyldimethoxysilane to 75%wt ethanol aqueous solution, ultrasonically disperse at a frequency of 50kHz for 30 minutes, add nano zinc oxide, the mass ratio of γ-chloropropylmethyldimethoxysilane, 75%wt ethanol aqueous solution, and nano zinc oxide is 18:300:81, react at 75°C for 8h, filter after the reaction, wash with ethanol 3 times, and place in a vacuum drying oven at 50°C for 24h to obtain chlorinated modified nano zinc oxide; Add oleic acid amide, chlorinated modified nano zinc oxide and azobisisobutyronitrile into ethyl acetate, wherein the mass ratio of oleic acid amide, chlorinated modified nano zinc oxide, ethyl acetate and azobisisobutyronitrile is 8:2:180:0.08, and stir and disperse at a speed of 300 r / min for 30 minutes to obtain an antibacterial finishing agent; The antibacterial cotton fiber fabric is used as the inner layer fabric, the ecological cotton is used as the middle layer fabric, and the flame-retardant antistatic polyamide fiber fabric is used as the outer layer fabric. The inner layer fabric, the middle layer fabric, and the outer layer fabric are sewn and compounded by polyester thread to obtain a wear-resistant and antibacterial multi-layer composite fabric.

[0030] In the above embodiments and comparative examples, nano zinc oxide was purchased from Shanghai Yaotian New Materials Technology Co., Ltd., with article number: YT-Oy-02-2 and an average particle size of 50 nm; graphene is graphene oxide nanosheets purchased from Shanghai Naio Nanotechnology Co., Ltd. with article number: NO-C-068-1, with a thickness of <2 nm and a diameter of <20 μm; polyaniline was purchased from Guangdong Shengke Biochemical Technology Co., Ltd. with a grade of analytical grade AR, CAS: 25233-30-1; polyamide resin is polyamide 6 purchased from Dongguan Yiyuan Plastic Raw Materials Co., Ltd. with article number: 20211021; cotton fiber was purchased from Binzhou Shengchi Trading Co., Ltd. with a fiber length of 30 mm; and ecological cotton was purchased from Shandong Aorong Garment Co., Ltd. with a gram weight of 300 g / m 2 ; Polyester thread was purchased from Yiwu Najie Weaving Co., Ltd., item number: 002010, parameter: 40S / 2.

[0031] Test Case (1) Antistatic performance: The antistatic performance of the flame-retardant antistatic polyamide fiber fabrics prepared in Examples 2-6 and Comparative Examples 1-2 was measured with reference to the standard GB / T12703.2-2009 "Evaluation of electrostatic properties of textiles Part 2: Charge surface density". The measurement results of charge surface density are shown in Table 1: Table 1

[0032] As shown in Table 1, the flame retardant antistatic polyamide fiber fabric prepared by the present invention has good antistatic performance. When preparing the flame retardant antistatic composite material, the introduction of graphene oxide and polyaniline can effectively improve the antistatic performance of the fabric. After epoxy modification, graphene oxide can be chemically bonded with melamine molecules. Melamine-graphene oxide and polyaniline react with the phosphorus oxychloride group on the pentaerythritol bisphosphate diphosphoryl chloride molecule through the amino group and imino group on the molecule, realizing the chemical crosslinking between melamine-graphene oxide, polyaniline and pentaerythritol bisphosphate diphosphoryl chloride. Through the entanglement of the crosslinked product and the polyamide molecular chain, the compatibility and dispersion uniformity of each effective component in the polyamide resin are improved, and the antistatic effect is good. Compared with Example 2, the antistatic component in Comparative Example 1 does not undergo chemical crosslinking, the compatibility and dispersion uniformity in the polyamide resin are reduced, and the antistatic performance is weakened.

[0033] (2) Flame retardant properties: The flame retardant properties of the flame retardant antistatic polyamide fiber fabrics prepared in Examples 2-6 and Comparative Examples 1-2 were measured with reference to the standard GB / T5454-1997 "Textile Combustion Performance Test Oxygen Index Method". The results of the measurement of the limiting oxygen index (LOI) are shown in Table 2: Table 2

[0034] As shown in Table 2, the flame retardant and antistatic polyamide fiber fabric prepared by the present invention has good flame retardant properties. In the case of flame retardant and antistatic composite materials, the introduction of phosphate, melamine and graphene oxide can effectively improve the flame retardant properties of the fabric. After epoxy modification, graphene oxide can be chemically bonded with melamine molecules. Melamine-graphene oxide and polyaniline react with the phosphorus oxychloride groups on the pentaerythritol bisphosphate diphosphoryl chloride molecules through the amino and imino groups on the molecules, thereby achieving chemical crosslinking between melamine-graphene oxide, polyaniline and pentaerythritol bisphosphate diphosphoryl chloride. The crosslinked products are then bonded to the polyamide molecular chains. The entanglement of graphene oxide improves the compatibility and uniformity of dispersion of each effective component in the polyamide resin, and has a good flame retardant effect. In addition, during the epoxy modification process of graphene oxide, silicone is introduced. When the polymer material burns, the silicone will migrate to the surface of the burning material to form a silicon-rich layer, and the combustion generates an inorganic oxygen-isolating protective layer containing -Si-O-bonds and -Si-C-bonds, which can not only prevent the volatiles generated by the combustion from escaping, but also inhibit the thermal cracking of the polymer material, and effectively prevent the melt from dripping, which can effectively enhance the flame retardant properties of the fabric. Compared with Example 2, the flame retardant component in Comparative Example 1 does not undergo chemical crosslinking, and its compatibility and uniformity of dispersion in the polyamide resin are reduced, and silicone is obviously introduced, and the antistatic performance is significantly weakened.

[0035] (3) Antibacterial performance: The antibacterial performance of the antibacterial cotton fiber fabrics prepared in Examples 2-6 and Comparative Examples 1-2 was measured with reference to the standard FZ / T73023-2006 "Antibacterial Knitwear". The antibacterial rates of the fabrics before washing and after washing 50 times were measured respectively. The results are shown in Table 3: Table 3

[0036] As shown in Table 3, the antibacterial cotton fiber fabric prepared by the present invention has good antibacterial properties. When preparing the antibacterial finishing agent, the introduction of nano zinc oxide can effectively improve the antibacterial properties of the fabric. The nano zinc oxide reacts with γ-chloropropylmethyldimethoxysilane to obtain chlorinated modified nano zinc oxide; oleic acid reacts with dichlorothionyl to obtain oleic acid chloride, and the acyl chloride group on the oleic acid chloride molecule reacts with the imino group on the diallylamine molecule to convert the imino group into a tertiary amine, and the tertiary amine reacts with the chlorinated modified nano zinc oxide to generate an antibacterial quaternary ammonium salt, and the antibacterial properties are further improved; the carbon-carbon double bonds in the oleic acid molecule and the carbon-carbon double bonds on the diallylamine molecule can be cured and cross-linked in the pores and surface of the cotton fiber fabric base cloth under the action of a photoinitiator and under ultraviolet irradiation, so that the fabric has a lasting and stable antibacterial property. Compared with Example 2, in Comparative Example 2, the chlorinated nano zinc oxide did not chemically bond with oleamide, i.e., no quaternary ammonium salt was formed, and the antibacterial property was reduced. The binding force between the chlorinated nano zinc oxide and the fabric mainly depended on the adsorption of the chlorinated nano zinc oxide by the fabric and the coating of the cross-linked product of the double bonds in the oleamide molecules. As the number of washings increased, the nano zinc oxide gradually fell off, and the antibacterial property was significantly reduced.

[0037] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a wear-resistant and antibacterial multi-layer composite fabric, characterized in that: The following steps are involved: Step 1, mixing pentaerythritol and phosphorus oxychloride, reacting, cooling, filtering, washing, and drying after the reaction is completed to obtain pentaerythritol bisphosphate diphosphoryl chloride; Step 2: adding melamine into deionized water, heating and dissolving, adjusting the pH value to 9-10, adding epoxy-modified graphene oxide, reacting, filtering, washing, and drying after the reaction is completed to obtain melamine-graphene oxide; Adding polyaniline to N-methylpyrrolidone, stirring and dissolving, adding melamine-graphene oxide and pyridine, ultrasonically dispersing, adding pentaerythritol diphosphate diphosphoryl chloride, reacting, cooling after the reaction, filtering, washing, and drying to obtain a flame retardant and antistatic composite material; Step 3, mixing the flame retardant antistatic composite material with the polyamide resin, and melt spinning to obtain the flame retardant antistatic polyamide fiber; Step 4, spinning the flame retardant antistatic polyamide fiber into yarn, and then spinning the yarn into fabric to obtain the flame retardant antistatic polyamide fiber fabric; Step 5, spinning the cotton fiber into yarn, and then spinning the yarn into fabric to obtain a cotton fiber fabric base cloth; The cotton fiber fabric base fabric is impregnated in an antibacterial finishing agent, double-impregnated and double-rolled, cured, washed, and dried to obtain an antibacterial cotton fiber fabric; The antibacterial cotton fiber fabric is used as the inner layer fabric, the ecological cotton is used as the middle layer fabric, and the flame-retardant antistatic polyamide fiber fabric is used as the outer layer fabric. The inner layer fabric, the middle layer fabric, and the outer layer fabric are compounded to obtain a wear-resistant and antibacterial multi-layer composite fabric.

2. The method for preparing a wear-resistant and antibacterial multi-layer composite fabric according to claim 1, characterized in that: In the step 1, the molar ratio of pentaerythritol to phosphorus oxychloride is 1:(2-2.2), and the reaction conditions are reflux reaction at 95-105° C. for 5-7 hours.

3. The method for preparing a wear-resistant and antibacterial multi-layer composite fabric according to claim 1, characterized in that: In the step 2: when preparing melamine-graphene oxide, the mass ratio of melamine, deionized water, and epoxy-modified graphene oxide is 12.6:(300-400):(8-10), and the reaction conditions are 85-95° C. for 5.5-6.5 hours; Wherein, the epoxy-modified graphene oxide is prepared by the following steps: The graphene oxide is added to an ethanol aqueous solution, and after ultrasonic dispersion, γ-glycidyloxypropyltrimethoxysilane is added dropwise to react. After the reaction is completed, the reaction is filtered, washed, and dried to obtain epoxy-modified graphene oxide; The mass ratio of the graphene oxide, the ethanol aqueous solution and γ-glycidyloxypropyltrimethoxysilane is 20:(400-600):(8-12), and the reaction conditions are reflux reaction at a temperature of 70-80° C. for 8-12 hours.

4. The method for preparing a wear-resistant and antibacterial multi-layer composite fabric according to claim 1, characterized in that: In the step 2: when preparing the flame retardant antistatic composite material, the mass ratio of polyaniline, N-methylpyrrolidone, melamine-graphene oxide, pyridine, and pentaerythritol bisphosphate diphosphoryl chloride is (72.7-76.3):(1000-1500):(15-20):(8-12):(20-30), and the reaction conditions are to react at a temperature of 60-80°C for 8-10 hours.

5. The method for preparing a wear-resistant and antibacterial multi-layer composite fabric according to claim 1, characterized in that: In the step 3, the mass ratio of the flame retardant antistatic composite material to the polyamide resin is (6-10):100, and the temperature of the melt spinning is 260-280°C.

6. The method for preparing a wear-resistant and antibacterial multi-layer composite fabric according to claim 1, characterized in that: In step 4, the yarn count of the yarn is 30-50S, and the weight of the flame-retardant antistatic polyamide fiber fabric is 180-220g / m 2 .

7. The method for preparing a wear-resistant and antibacterial multi-layer composite fabric according to claim 1, characterized in that: In step 5, the yarn count of the yarn is 40-60S, and the weight of the cotton fiber fabric base fabric is 160-180g / m 2 .

8. The method for preparing a wear-resistant and antibacterial multi-layer composite fabric according to claim 1, characterized in that: In the step 5, the bath ratio of the cotton fiber fabric base cloth to the antibacterial finishing agent is 1:(15-25), and the curing condition is irradiation under ultraviolet light with a wavelength of 254nm for 5-10min; Wherein, the antibacterial finishing agent is prepared by the following steps: S1. Add thionyl chloride dropwise to oleic acid under stirring, react after the addition is complete, and purify after the reaction to obtain oleic acid chloride; S2. adding diallylamine to toluene, stirring and dispersing, and then dropping oleic acid chloride, and after the dropping is complete, reacting, and after the reaction is complete, purifying to obtain oleic acid amide; S3. Add γ-chloropropylmethyldimethoxysilane to an ethanol aqueous solution, and after ultrasonic dispersion, add nano zinc oxide to react. After the reaction is completed, filter, wash, and dry to obtain chlorinated modified nano zinc oxide; The chlorinated modified nano zinc oxide is added to ethanol, ultrasonically dispersed, and then oleic acid amide and potassium iodide are added to react. After the reaction is completed, the reaction is filtered, washed, and dried to obtain a quaternary ammonium antibacterial agent. S4. Add the quaternary ammonium antibacterial agent and azobisisobutyronitrile into ethyl acetate, stir and disperse, and obtain an antibacterial finishing agent.

9. The method for preparing a wear-resistant and antibacterial multi-layer composite fabric according to claim 8, characterized in that: In S1, the molar ratio of oleic acid to thionyl chloride is 1:(1-1.2), and the reaction conditions are to react at a temperature of 25-35°C for 1.5-2.5h; in S2, the mass ratio of toluene to diallylamine is 1:(10-20), the molar ratio of diallylamine to oleic acid chloride is (1-1.1):1, and the reaction conditions are to reflux at a temperature of 110-120°C for 8-12h; in S3, when preparing chlorinated modified nano zinc oxide, the mass ratio of γ-chloropropylmethyldimethoxysilane, ethanol aqueous solution, and nano zinc oxide is (15-20):( 250-350):81, the reaction conditions are 6-10h at 70-80°C. When preparing the quaternary ammonium antibacterial agent, the mass ratio of chlorinated modified nano zinc oxide, ethanol, oleic acid amide and potassium iodide is (8.8-9.2):(80-120):(36.2-38):(0.05-0.11), and the reaction conditions are 20-30h at 75-85°C. In S4: the mass ratio of quaternary ammonium antibacterial agent, ethyl acetate and azobisisobutyronitrile is (8-13):(150-200):(0.06-0.1).

10. A wear-resistant and antibacterial multi-layer composite fabric prepared by the method for preparing a wear-resistant and antibacterial multi-layer composite fabric according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Antistatic flame-retardant nylon

    CN103360755B

  • Bacteria resistant cotton fiber or cotton fabric and preparation method

    CN1306102C

Cited By

  • Polyurethane-based porous composite wave-absorbing material and preparation method thereof

    CN120005144A

  • Antibacterial moisture-absorption breathable pure cotton fabric, preparation method and application in non-sensitization underwear

    CN120680765A